Semaphorin-Mediated Corticospinal Axon Elimination Depends on the Activity-Induced Bax/Bak-Caspase Pathway - Gu, Zirong (J Neurosci, 2020)
Axon guidance molecules and neuronal activity have been implicated in the establishment and refinement of neural circuits during development. It is unclear, however, whether these guidance molecule- and activity-dependent mechanisms interact with one another to shape neural circuit formation. The formation of corticospinal (CS) circuits, which are essential for voluntary movements, involves both guidance molecule- and activity-dependent components during development. We previously showed that semaphorin6D (Sema6D)-plexinA1 (PlexA1) signaling eliminates ipsilateral projections of CS neurons in the spinal cord, while other studies demonstrate that CS projections to the spinal cord are eliminated in an activity-dependent manner. Here we show that inhibition of cortical neurons during postnatal development causes defects in elimination of ipsilateral CS projections in mice. We further show that mice that lack the activity-dependent Bax/Bak pathway or caspase-9 similarly exhibit defects in elimination of ipsilateral CS projections, suggesting that the activity-dependent Bax/Bak-caspase-9 pathway is essential for the removal of ipsilateral CS projections. Interestingly, either inhibition of neuronal activity in the cortex or deletion of Bax/Bak in mice causes a reduction in PlexA1 protein expression in corticospinal neurons. Finally, intracortical microstimulation induces activation of only contralateral forelimb muscles in control mice, whereas it induces activation of both contralateral and ipsilateral muscles in mice with cortical inhibition, suggesting that the ipsilaterally projecting CS axons that have been maintained in mice with cortical inhibition form functional connections. Together, these results provide evidence of a potential link between the repellent signaling of Sema6D-PlexA1 and neuronal activity to regulate axon elimination. SIGNIFICANCE STATEMENT Both axon guidance molecules and neuronal activity regulate axon elimination to refine neuronal circuits during development. However, the degree to which these mechanisms operate independently or cooperatively to guide network generation is unclear. Here, we show that neuronal activity-driven Bax/Bak-caspase signaling induces expression of the PlexA1 receptor for the repellent Sema6D molecule in corticospinal neurons (CSNs). This cascade eliminates ipsilateral projections of CSNs in the spinal cord during early postnatal development. The absence of PlexA1, neuronal activity, Bax and Bak, or caspase-9 leads to the maintenance of ipsilateral projections of CSNs, which can form functional connections with spinal neurons. Together, these studies reveal how the Sema6D-PlexA1 signaling and neuronal activity may play a cooperative role in refining CS axonal projections.